2016
DOI: 10.1007/s12035-016-9997-9
|View full text |Cite
|
Sign up to set email alerts
|

The Neuron-Specific Protein TMEM59L Mediates Oxidative Stress-Induced Cell Death

Abstract: TMEM59L is a newly identified brain-specific membrane-anchored protein with unknown functions. Herein we found that both TMEM59L and its homolog, TMEM59, are localized in Golgi and endosomes. However, in contrast to a ubiquitous and relatively stable temporal expression of TMEM59, TMEM59L expression was limited in neurons and increased during development. We also found that both TMEM59L and TMEM59 interacted with ATG5 and ATG16L1, and that overexpression of them triggered cell autophagy. However, overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…TMEM59 (also known as dendritic cell-derived factor 1, DCF1) is a ubiquitously expressed type I transmembrane protein. TMEM59 contains an ATG16L1-binding motif that promotes local activation of LC3 and evokes autophagy 41,42 . Previous studies suggested that TMEM59 could regulate neural stem cell differentiation 43,44 , dendritic spine development 45 , neuropeptide expression 46 , glioblastoma cell proliferation/apoptosis 47,48 , the Wnt signaling through interacting with the Wnt receptor Frizzled (FZD) 49 , and glycosylation and processing of the Alzheimer-associated Aβ precursor protein 50 .…”
Section: Introductionmentioning
confidence: 99%
“…TMEM59 (also known as dendritic cell-derived factor 1, DCF1) is a ubiquitously expressed type I transmembrane protein. TMEM59 contains an ATG16L1-binding motif that promotes local activation of LC3 and evokes autophagy 41,42 . Previous studies suggested that TMEM59 could regulate neural stem cell differentiation 43,44 , dendritic spine development 45 , neuropeptide expression 46 , glioblastoma cell proliferation/apoptosis 47,48 , the Wnt signaling through interacting with the Wnt receptor Frizzled (FZD) 49 , and glycosylation and processing of the Alzheimer-associated Aβ precursor protein 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Although we show that TMEM59 expression also diminishes glycan modification of FZD, we were unable to link these glycosylation alterations to the Wnt-potentiating activity of TMEM59. In addition, TMEM59 was reported to induce unconventional autophagy in response to bacterial infection and to promote apoptotic cell death in neuronal cells ( 47 , 55 , 56 ). Both these functions require the TMEM59 intracellular domain that is dispensable for its role in Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…First, the expression level of TMEM59 varies among tissues, which might affect its role in Wnt signaling regulation in different tissue contexts ( 47 ). Second, the molecular activity of TMEM59 might display redundancy with the highly homologous gene TMEM59-like (TMEM59L) ( 56 ). Third, in contrast to core Wnt pathway components, a sensitized genetic background might be required for gene deletion approaches to reveal the biological role of TMEM59, as shown for other recently identified Wnt signaling modifiers ( 72 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…Viral gene therapy vectors specifically designed for NDD applications should be able to efficiently cross the blood-brain barrier (BBB), if delivered by iv infusion [44,49], and support an efficient transgene expression, regardless of aberrant cell signaling caused by the accumulation of toxic proteins or restoration of an autophagic state in neuronal cells [50]. For instance, vectors based on genomes of adeno-associated virus (AAV) [44,49,[51][52][53][54][55][56], lentivirus [57], type 1 herpes simplex virus [58], and Semliki Forest virus (SFV) [59] have been broadly used for neuron targeting. Extensive use of the above viruses in neuroscience is dictated by their natural ability to efficiently and selectively transduce and provide high transgene expression in neurons.…”
Section: Choosing An Ideal Vectormentioning
confidence: 99%